Religious Freedom in World Politics: : A Linchpin for Global Peace - Eko Ernada (ADP Publisher, 2024)
Religious freedom is a fundamental human right enshrined in numerous international declarations and constitutions. Despite its universal recognition, religious persecution and discrimination persist in various parts of the world, often leading to conflict and instability. This paper explores the intricate relationship between religious freedom and global peace, arguing that fostering religious freedom is crucial for achieving sustainable peace on a global scale. Drawing on historical examples, empirical evidence, and theoretical frameworks, this paper examines how religious freedom promotes tolerance, pluralism, and social cohesion, thereby mitigating intergroup tensions and contributing to peaceful coexistence among diverse communities. Furthermore, it analyzes the role of state actors, international organizations, and civil society in advancing religious freedom agendas. It addresses the challenges and opportunities in promoting this fundamental right in world politics. By elucidating the importance of religious freedom as a linchpin for global peace, this paper seeks to provide insights for policymakers, scholars, and practitioners to prioritize and advocate for religious freedom in their respective spheres.